Rapid, multiplexed detection of biomolecules using electrically distinct hydrogel beads. Issue 13 (3rd June 2020) - Cowell, Thomas W.; Valera, Enrique; Jankelow, Aaron; Park, Joonhyuck; Schrader, Alex W.; Ding, Ruihua; Berger, Jacob; Bashir, Rashid; Han, Hee-Sun
Abstract : Electrically distinct microparticles enable rapid, versatile, and multiplexed electrical detection of biomolecules using Coulter counting-based detection. Abstract : Rapid, low-cost, and multiplexed biomolecule detection is an important goal in the development of effective molecular diagnostics. Our recent work has demonstrated a microfluidic biochip device that can electrically quantitate a protein target with high sensitivity. This platform detects and quantifies a target analyte by counting and capturing micron-sized beads in response to an immunoassay on the bead surface. Existing microparticles limit the technique to the detection of a single protein target and lack the magnetic properties required for separation of the microparticles for direct measurements from whole blood. Here, we report new precisely engineered microparticles that achieve electrical multiplexing and adapt this platform for low-cost and label-free multiplexed electrical detection of biomolecules. Droplet microfluidic synthesis yielded highly-monodisperse populations of magnetic hydrogel beads (MHBs) with the necessary properties for multiplexing the electrical Coulter counting on chip. Each bead population was designed to contain a different amount of the hydrogel material, resulting in a unique electrical impedance signature during Coulter counting, thereby enabling unique identification of each bead. These monodisperse bead populations span a narrow range of sizes ensuring that all can be captured sensitively and selectively under simultaneously flow. Incorporating these newly synthesized beads, we demonstrate versatile and multiplexed biomolecule detection of proteins or DNA targets. This development of multiplexed beads for the electrical detection of biomolecules, provides a critical advancement towards multiplexing the Coulter counting approach and the development of a low cost point-of-care diagnostic sensor.